Poetry Reader for Russian Learners - Titus, Julia; Moore, Mario; McIntosh, Wayde (Yale University Press, 2015)
Through the poetry of nineteenth- and twentieth-century Russian authors, including Pushkin and Akhmatova, Poetry Reader for Russian Learners helps upper-beginner, intermediate, and advanced Russian students refine their language skills. Poems are coded by level of difficulty. The text facilitates students' interaction with authentic texts by means of a complete set of learning tools, including biographical sketches of each poet, stress marks, annotations, exercises, questions for discussion, and a glossary. An ancillary Web site containing audio files for all poems can be found below.